A firm-level investigation of innovation in the Caribbean: A comparison of manufacturing and service firms - Antonio Alleyne; Troy Lorde; Quinn Weekes (Economies, 2017)
A lack of growth remains a major concern for Caribbean countries. Private sector development has been identified as vital in addressing this problem. Innovation, a necessary condition for competitiveness, is a key channel through which the private sector can help to stimulate growth. An analysis of innovation at the firm level for Caribbean manufacturing and services sectors shows that patent rights, the level of domestic sales, collaboration for innovation purposes, innovation intensity (that is, the efficiency with which innovation funds are managed), availability of technology, knowledge about new market trends, domestic sales, and the size of the workforce are critical to the innovation process in both sectors. Several differences also exist. Innovative service firms are older, in contrast to manufacturing firms, which tend to be younger; foreign ownership is key for service firms; and both types of firms face different obstacles to innovation. Policymakers should tailor policies that take such differences into account.
Keywords: C55; O14; O30; 330; innovation; firm level; Caribbean; manufacturing; services